Neotropical freshwater crabs (Decapoda: Pseudothelphusidae) shred leaves - Yang, Carol (2020)
Freshwater crabs are macroconsumers that are commonly found in Neotropical headwater streams that may play a key role in energy flow and nutrient cycling in detrital food webs. Although studies have examined the feeding habits of trichodactylid crabs, little is known of this behavior in pseudothelphusid species, and specifically whether they actually consume leaf material. We conducted three nine-day laboratory trials with pseudothelphusid crabs (Ptychophallus tumimanus (Rathbun, 1898)) and leaves (Koanophyllon pittieri) to investigate whether crabs shred leaves. We hypothesized that leaf mass loss would be faster with crabs present relative to control tanks with only leaves. Leaf mass loss was significantly higher (p < 0.001) in tanks with crabs (0.49 ± 0.07 g, mean ± 1 SD) compared to control tanks (0.31 ± 0.05 g). We observed crabs manipulating, shredding, and consuming leaves, with leaf fragments and egesta present in tanks with crabs but not in control tanks. Their consumption and egestion activity may affect nutrient availability and transformation by stimulating microbial activity during leaf breakdown and converting coarse particulate organic matter (CPOM) to fine particulate organic matter (FPOM). Therefore, freshwater crabs need to be considered when studying energy flow and nutrient cycling in detrital food webs of Neotropical headwater streams.